Fonoaudiologia : Contribuições nos estudos forenses de comparação de locutores - Miquilussi, Paloma Alves; Koslovski, Marilisa Exter; Carneiro, Denise de Oliveira (Language and Law / Linguagem e Direito, 2017)
This research was motivated by the growing demand for speechpathologists to act as forensic experts, particularly in cases of speaker comparison. A literature search discovers very little about speech-language pathologists working as forensic experts. Thus, the search was widened to include the science of Speech-Language Pathology, the national curricula for Bachelor degrees in Speech-Language Pathology and the work of forensic experts in the area of speaker comparison. The results showed that human communication is one of the objects of study of the speech-language pathologist, and that work in forensic speaker comparison uses parameters standardly analyzed by speech-language pathologists and that forensic expertise in this area is enriched through multidisciplinary. Hence, it follows that the inclusion of speech-language pathologists in multidisciplinary teams working on forensic speaker comparison is amply justifiable.